Estimating the density of molten CaF2-Al2O3-CaO slags based on optical basicity - Birol, B.; Saridede, M. N. (SOC MINING METALLURGY EXPLORATION INC, 2016)
Slag density is a significant factor in determining the process efficiency of the electroslag remelting (ESR) process, where calcium fluoride (CaF2)-based slag is formed synthetically to refine metal ingots. Although there are some former studies investigating the density of CaF2-containing slags, the prediction models focusing on them are applicable only to some specific systems. The present study aims to build a model to predict density for a wide range of CaF2-containing ESR slags. To investigate density for various slag compositions, CaF2-Al2O3-based and CaF2-Al2O3-CaO-based slag compositions were prepared. Additionally, some minor constituents like FeO, MgO and MnO were added to a 5:3:2 CaF2-Al2O3-CaO slag in order to investigate the effects of these constituents on the slag. The volumes of the prepared slags were measured in a tube furnace at 1450-1550 degrees C using the sessile drop technique, and their densities were calculated. The results showed that for the slags, density is related to optical basicity, and therefore a prediction model based on an Arrhenius equation was built. The model was tested with data from literature, and its limitations and validity are discussed.
Keywords: Density; Optical basicity; CaF2-Al2O3-CaO slag; Modeling; PHYSICAL-PROPERTIES; LEWIS BASICITY; MOLAR VOLUMES; GLASSES; SALTS; MELTS; MODEL; Metallurgy & Metallurgical Engineering; Mining & Mineral Processing